A Study of hotel and property sectors in Malaysia: Developers’ views and selected analyses of price drivers - Ariff, Mohamed *; Cheong, Calvin W. H. *; Mohd Thas Thaker, Hassanudin * (2021)
This paper reports an assessment of supply-demand side economics of hotel and property sectors, while it also examines the pricing behavior of the real estate sector in Malaysia. First economic fact about the hotel sector is that it has been carefully developed over several decades, and forms an important destination point for international travelers attracting about 26 million visitors with demands ranging from simple hotel services to the most exotic private chalets. This sector has gone through a decline since 2017 and has been made worse by the Covid Pandemic. Analyses of the property sector provide interesting, unexpected finding that price increases in residential units have kept pace with inflation in the country, and that further localizing production of input materials, supply of more land regulatory consolidation would help the industry. Nonetheless, the supply of built units in recent years falls short of national policy aim to provide affordable housing because supply is 22 percent facing a demand closer to 40 percent at costs less than RM250,000. Some insights are gained from examining the broader price drivers other than inflation to understand how the economics of the property sector is shaping up the real estate economy. There is a body of relevant findings to be refined further for policy consideration to address affordable housing issue, for more l to be made available (as is done in Melbourne Australia, as an example),a nd finally to build local capacity to produce quality items that are currently imported.